ANDROGEN INSENSITIVITY SYNDROME DUE TO NON-CODING VARIATION IN THE ANDROGEN RECEPTOR GENE: REVIEW OF THE LITERATURE AND CASE REPORT OF A PATIENT WITH MOSAIC C.-547c>T variant - Noveski, Predrag; Plasheski, Tosho; Dimitrovska, Maja; Plaseska-Karanfilska, Dijana (De Gruyter, 2023)
Sexual development (SD) is a complex process with strict spatiotemporal regulation of gene expression. Despite advancements in molecular diagnostics, disorders of sexual development (DSD) have a diagnostic rate of ∼50%. Androgen insensitivity syndrome (AIS) represents the most common form of 46,XY DSD, with a spectrum of defects in androgen action. Considering the importance of very strict regulation of the SD, it is reasonable to assume that the genetic cause for proportion of the DSD lies in the non-coding part of the genome that regulates proper gene functioning. Here we present a patient with partial AIS (PAIS) due to a mosaic de novo c.-547C>T pathogenic variant in the 5’UTR of androgen receptor (AR) gene. The same mutation was previously described as inherited, in two unrelated patients with complete AIS (CAIS). Thus, our case further confirms the previous findings that variable gene expressivity could be attributed to mosaicism. Mutations in 5’UTR could create new upstream open reading frames (uORFs) or could disrupt the existing one. A recent systematic genome-wide study identified AR as a member of a subset of genes where modifications of uORFs represents an important disease mechanism. Only a small number of studies are reporting non-coding mutations in the AR gene and our case emphasizes the importance of molecular testing of the entire AR locus in AIS patients. The introduction of new methods for comprehensive molecular testing in routine genetic diagnosis, accompanied with new tools for in sillico analysis could improve the genetic diagnosis of AIS, and DSD in general.
Keywords: Androgen insensitivity syndrome (AIS); 5’UTR variant; upstream open reading frames (uORFs); non-coding variation; mosaicism